PAHAM INKAR AS-SUNNAH DAN PROPAGANDANYA TENTANG HADIS NABI SAW (STUDI KRITIS TERHADAP PANDANGAN INKAR AS-SUNNAH TENTANG KEDUDUKAN DAN KEHUJJAHAN HADIS NABI SAW) - Faridi Faridi; Imam Sucipto; Engkos Kosasih (IAIN Syekh Nurjati Cirebon, 2023)
This research aims to answer the accusations of the Inkar as-Sunnah who rejectthe hadiths of the Prophet, either in whole or in part. This study used the libraryresearch method by tracing and examining the books of scholars, journal articles,youtube etc. There are two very basic doubts argued by munkiru as-Sunnah inaccording with this problem; namely first, the inauthenticity of hadith since it hadbeen only written after the Prophet Muhammad died, so that they only adhered tothe Qur’an as a source of Islamic teachings and second, the rejection of hadithĀhād for its poorness of trustworthy. These two doubts are answered, first by thefact that some of the Prophet's companions had written hadith since he still alive.Meanwhile, the following doubts are disputed by the validity of religious teachings,even though only conveyed by one or two men.